Anatolij Oleksandrovych Lobenko - "ORTHOPAEDICS, TRAUMATOLOGY AND PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is dedicated to the memory of the famous scientist, doctor, public figure, academician of the National Academy of Medical Sciences of Ukraine, Doctor of Medical Sciences, Professor Anatolij Oleksandrovych Lobenko.